Pengaruh Pelatihan Metode Prices Terhadap Pengetahuan Dan Keterampilan Penanganan Cedera Strain Pada UKM KNC-Emergency - Handayani, Erna; Rima Agustin, Wahyu; Mustikarani, Innez Karunia; Nugroho, Singgih; Rizqiea, Noerma Shovie (Universitas Muhammadiyah Klaten, 2024)
Strain injuries are injuries caused by excessive stretch or tear of the muscles or tendons, calves, groin, hamstring muscles, back and legs. The first 24 hours of treatment can use Protect, Rest, Ice, Compression, Evaluation, and Support for this method (PRICES) will be given as quickly as possible. The type of research conducted is quantitative pre-experimental with the Quasy Experimental method with a one group pretest - posttes Without Control Group Design, namely given a pretest then given treatment in the form of material with PPT media and given training in the PRICES method, then given a posttest which serves to analyze the level of knowledge and skill level. This study used a sample of 37 respondents. In this study using Wilcoxon test analysis. The results of the study prove that the data obtained have significant changes in knowledge and skills after being given material and training on the PRICES method for KNC-E members with a p value of 0.000. The conclusion that can be drawn is that providing material and training on the PRICES method can improve the knowledge and skills of KNC-E members.